2003
DOI: 10.1093/bja/aeg114
|View full text |Cite
|
Sign up to set email alerts
|

Basal and nitroglycerin-induced exhaled nitric oxide before and after cardiac surgery with cardiopulmonary bypass

Abstract: The capacity of the lungs to increase exhaled NO in response to intravenous GTN is reduced after CPB, suggesting microvascular injury and/or atelectasis after routine open-heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
(28 reference statements)
3
23
0
1
Order By: Relevance
“…24 As a reference, Figure 1a depicts such a response in a patient undergoing bypass surgery before CPB. Figure 1b and c demonstrates that there is very little change in exhaled NO after GTN administration in lung transplant recipients when measured approximately 1 hour after reperfusion during hemostatic and hemodynamic stability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…24 As a reference, Figure 1a depicts such a response in a patient undergoing bypass surgery before CPB. Figure 1b and c demonstrates that there is very little change in exhaled NO after GTN administration in lung transplant recipients when measured approximately 1 hour after reperfusion during hemostatic and hemodynamic stability.…”
Section: Resultsmentioning
confidence: 99%
“…18,19,29 -32 Because basal exhaled NO mainly reflects the relatively large amount of NO release from the airway compartment, 33,34 we speculated that such changes in exhaled NO might represent airway epithelial cell dysfunction and/or oxidative stress in the vicinity of these cells. 24,26 To further investigate the fate of NO pathways in the microvascular lung compartment, one can deliver exogenous NO to the pulmonary circulation and monitor evolution of this NO in exhaled breath. 18,23,[35][36][37] We have suggested that GTN-induced exhaled NO might be a useful tool to monitor metabolic function of the pulmonary microvasculature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations